Factores protectores y de riesgo en la calidad de vida y apoyo familiar de los diabéticos de 40 a 79 años. Loja. 2016. - Capa Paladines, Luis Paul (2017)
The people with diabetes mellitus experiment an important decrease in their quality of life compared with healthy people. This study took place in the city of Loja (Ecuador). It´s proposal was to evaluate the quality of life in patients with diabetes mellitus type II, considering socioeconomic, demographic and clinical characteristics. It is about an analytic study of cases and controls of cross section; the cases are represented by diabetes type II patients who presented complications and the control cases are for those diabetics who do not exhibit complications. The information was collected through the application of a previously validated instrument and it consists of socioeconomic demographic and clinical characteristics. The quality of life related with health (DQOL), made up of five general dimensions associated in a relevant or in a direct way to the type II mellitus diabetes and its treatment. Investigators assessed 500 people with diabetes, they find out there is significant statistical relationship between the quality of life and physical inactivity, no adhesion to the treatment, family dysfunction, depression, anxiety and stress, when evaluating the quality of life related with the diabetes mellitus II patients health, it´s observed that despite the studied group tends to have a good quality of life, a very important percentage reports a bad quality of life, situation that shows up the impact of the sickness over the physical inactivity and the poor adherence to the treatment with the appearance of the different complications in a short and in a long term. Key words: Chronic disease, physical inactivity, no-adhesion to the treatment, family dysfunction, stress, depression, anxiety.